Nilai-Nilai Moral Islami dalam Serat Wulang Reh - Endang Nurhayati (Millah: Journal of Religious Studies, 2010)
The article elaborates the Islamic moral values on Serat Wulang Reh. The Serat is one of works of Ingkang Sinuhun Paku Buwana IV containing moral education for Javanese society based on Islamic insights. The work contains wulang (read: advice) toward family and society at the time. Although it refers to the time, this serat can be reviewed. Since the sources of the serat are from Al Qur’an and Hadits, its values are useful as learning sources and moral guidance for future generation.